Description of acute and chronic load, training monotony and strain over a season and its relationships with well-being status: A study in elite under-16 soccer players - Nobari, H.; Aquino, R.; Clemente, F. M.; Khalafi, M.; Adsuar, J. C.; Pérez-Gómez, J. (Physiology & Behavior, 2020)
This study described the weekly variations of acute (wAL), chronic (wCL), acute:chronic workload ratio (wACWR), training monotony (wTM), and training strain (wTS) of perceived load, such as wellness indicators over a competitive season. In addition, we analyzed the associations between training load metrics and weekly reports. Twenty-nine under 16 years old elite players were daily monitored for 20 consecutive weeks during the season by individual observations. Training and match load were obtained using the session rating of perceived exertion. Well-being status relative to stress, fatigue, delayed onset muscle soreness (DOMS), and sleep quality/disorders were daily monitored using the Hooper index method. The results revealed that the highest values of wAL, wCL, and wTS were verified in the mid-season and the lowest values in the start-season. The highest values of accumulated weekly fatigue, stress, and DOMS were observed in the end-season, and the lowest values of sleep and stress in the start-season while the lowest values of fatigue and DOMS were observed in the mid-season. Regarding the load variability, the results showed the highest values between-week variations to wTS (15%; week-8 to 9) and the lowest reduction to wACWR (-19%; week-9 to 10). The highest within-week variations were verified to wACWR (coefficient of variation =19%; week-18) and the lowest to wCL (coefficient of variation =6%, week-19). Wellness indicators were moderate-large related to acute load, monotony and strain (r = 0.46-0.67). Overall Hooper index was the best predictor of the acute load (R2 = 0.45). These results provide new insights for coaches and practitioners about perceived loads and well-being variations over a season in elite youth level.